Inovasi dan Kreativitas Pemilik Usaha Tradisional "Cobe-Cobe" dan "Batu Mesa" di Desa Lempang, Barru - Padli, Sul; Aulia, Nurul; Ridha, Rasyid; W Suhaeb, Firdaus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the innovation and creativity of traditional cobekan and tombstone business owners in Tampung Cinae, Barru Regency. This study uses a qualitative approach with a case study design. The research subject only involved one informant, namely the business owner named Hariswan, who was determined through purposive sampling techniques. Data collection techniques through semi-structured interviews and participatory observation in the field. Data analysis was conducted using the Miles & Huberman interactive model with source triangulation and member checking techniques to ensure the validity of the findings. The results of the study indicate four main themes: (1) Background and Development of the Business, which reflects motivation and changes in the production process from manual to the use of modern tools; (2) Innovation and Product Development, in the form of incremental innovation through the use of tools such as grinders and excavators; (3) Product Creativity, seen from the variety of designs, colors, and motifs that follow market tastes; and (4) Business Risks and Challenges, including constraints of weather, raw materials, and work tools that are overcome with adaptive strategies. These findings confirm that traditional business innovation is based on local cultural experiences and values and has important implications for the empowerment of rural MSMEs.